Pembagian Waris Prioritas Perempuan Perspektif Maqasid Syariah dan Gender (Studi Pada Masyarakat Pendalungan Kabupaten Lumajang) - Hilmy Luayyin, Reza; Hidayah, Ulil; Ardli, M. Nabat (Jurnal Ilmiah Ekonomi Islam, 2024)
The focus of this research is on the problem of dividing the inheritance of the Pendalungan community with provisions for dividing sons and daughters that are different from the provi¬sions in Islamic Inheritance Law, where in Islam men and women receive a share of 2:1 while the tradition that occurs in the Pendalungan community is by prioritizing the share of inher¬itance in their daughters. This research method uses descriptive analysis by collecting data by random sampling in the Pendalungan community who have a livelihood from farming. Data analysis was carried out using the theory of justice and gender equality and the theory of mari¬tal law. The results shows that there was a tradition of an inheritance distribution system with women prioritizing based on the philosophy of the Pendalungan community that women should receive a higher priority scale in receiving inheritance distribution due to secondary differences that women are physically weaker in working on plantations than men. And the conclusions ob¬tained are 1) The distribution of inheritance by prioritizing women getting the most share is still being carried out by the people of Pendalungan Village. 2) Priority in women in the distribution of inheritance can be said to be good when viewed from the sociology side of Islamic law and the absence of social conflict even though it is very different with Islamic rules or Shari'a 3) The tradition of inheritance distribution by prioritizing women to get the most share is of course contrary to the concept of gender equality and justice because there is actually discrimination against men 4) Socio-historical and socio-cultural factors are more dominant than equality.